Nowruz Calendar and Its Emergence from Different Perspectives and Its Impact on Various Aspects of People’s Lives - Behzadi, Nina (Journal of History Culture and Art Research, 2017)
This paper is a brief research about the meaning of Nowruz from different perspectives and its impact on people’s interactions, which is celebrated at the dawn of spring in this ancient Iranian land. In different periods this ancient holiday has been seen with different opinions and its effects are all reflecting new life, happiness, love, blessing, birth, and growth, which are visible beautifully in nature. This paper is done by library and field studies and investigates the meanings and spiritual influences of this tradition in the culture, poetry, literature, philosophy, religious beliefs of the people of this land from the different perspectives (Islam - Zoroastrianism, etc.). By reviewing these theories on Nowruz and comparing it with present-day life, valuable results can be achieved so they can be used in the ups and downs of life.